RELATIONSHIP BETWEEN COMPLETE BASIC IMMUNIZATION STATUS AND SUSCEPTIBILITY TO ACUTE RESPIRATORY INFECTIONS (ARI) IN CHILDREN AGED 12-24 MONTHS - Engkus Kusnadi, Engkus Kusnadi; Andri Nugraha, Andri Nugraha; Andhika Lungguh Perceka, Andhika Lungguh Perceka; Amanda Sefani Ferantia, Amanda Sefani Ferantia (Jurnal Medika Cendikia, 2025)
Acute respiratory infections (ARI) are a significant health problem and a major cause of morbidity and mortality in children under five years of age in Indonesia. Complete basic immunization (IDL) is the most effective preventive intervention. However, CDI coverage in the Cibiuk Community Health Center (Puskesmas) area, Garut District, is very low (46.1% in 2022), which is thought to be strongly correlated with the high incidence of ARI in vulnerable age groups. This study aims to empirically analyze the relationship between Complete Basic Immunization status and the incidence of ARI in children aged 12-24 months. A retrospective case-control study involving 84 infants (42 ARI cases, 42 controls) with gender matching, using medical records and KIA books, analyzed with Chi-Square and Odds Ratio. Results: The majority of respondents (65.5%) had incomplete basic immunization. There was a highly significant association between immunization status and ARI incidence (p<0.05), with the risk of ARI being nearly 14 times greater in infants with incomplete immunization. Conclusion: Complete basic immunization status plays an important role in protecting infants aged 12–24 months from ARI. Therefore, increasing immunization coverage through promotional and preventive efforts needs to be intensified to reduce ARI morbidity in the Cibiuk Community Health Center working area.